Understanding the brain - Larson, Kristina; Larsen, Kristina; The Discovery Channel (Singapore: International Publishers Direct, 1999)
An overview of the basic structure and function of the human brain, and of selected areas of brain research which deal with memory, emotions, drugs, biofeedback
Executive producer, Nancy Lebrun ; editor, Sam Green
Narrator: Peter Coyote
Keywords: Brain